A Combined Topological ELF, NCI and QTAIM Study of Mechanism and Hydrogen Bond Controlling the Selectivity of the IMDC Reaction of Nitrone-alkene Obtained from m-allyloxybenzaldehyde - Chafaa, Fouad; Nacereddine, Abdelmalek K.; Djerourou, Abdelhafid (Letters in Organic Chemistry, 2020)
The selectivity and molecular mechanism of the intramolecular [3+2] cycloaddition (IMDC) reaction of nitrone-alkene generated from m-allyloxybenzaldehyde has been studied computationally using B3LYP/6-31G(d) theoretical method. The energy profiles indicate that this IMDC reaction favours kinetically the formation of the fused-endo, as observed experimentally. The solvent has no influence on the mechanism and selectivity, but it increases slightly the activation energy and decreases the exothermic character of this IMDC reaction. The analysis through electron localisation function (ELF) of the favourable fused-endo pathway shows that the formation of the C–O and C–C new bonds occurred via a non-concerted synchronous one-step mechanism. The analysis of noncovalent interaction using Non-covalent interaction (NCI) and QTAIM analyses of the structure of the fused-endo transition state indicates that the hydrogen-bond formed at this approach is the origin for the favouring of the fused-endo pathway.
Keywords: isoxazolidines